Analisis Technology Acceptance Model (TAM) pada Sistem E-Learning Universitas Advent Indonesia - Tabita Indri Siahaan; Elmor Benedict Wagiu (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
The e-learning system is one of the supporting elements in the teaching and learning process, where the process is carried out through internet media. The e-learning system used at the Universitas Advent Indonesia is Moodle. With this Moodle students can upload assignments and download lecture material provided by the lecturer. Whereas for lecturers can upload lecture material and download assignments that have been collected by the students. The purpose of this study are (1) To find out whether the entire menu in the Moodle has been used optimally or not, (2) to find out how the perception of benefits and ease of acceptance of users of the Moodle of the Adventist University of Indonesia. While the results of this study are (1) The acceptance of the Moodle at the Faculty of Information Technology Universitas Advent Indonesia was declared good, (2) the overall use of the menu in Moodle is not optimal yet, and (3) the perception of benefits and easiness influences user acceptance of Moodle.